Metabolic conditions and breast cancer risk among Los Angeles County Filipina Americans compared with Chinese and Japanese Americans. Issue 12 (6th September 2017) - Wu, Anna H.; Vigen, Cheryl; Butler, Lesley M.; Tseng, Chiu‐Chen
Abstract : Accumulating evidence suggests that the aggregation of common metabolic conditions (high blood pressure, diabetes and dyslipidemia) is a risk factor for breast cancer. Breast cancer incidence has risen steadily in Asian American women, and whether these metabolic conditions contribute to breast cancer risk in certain Asian American subgroups is unknown. We investigated the role of physician‐diagnosed hypertension, high cholesterol and diabetes separately, and in combination, in relation to the risk of breast cancer in a population‐based case–control study of 2, 167 Asian Americans diagnosed with breast cancer and 2, 035 age and ethnicity matched control women in Los Angeles County. Compared to Asian American women who did not have any of the metabolic conditions, those with 1, 2 or 3 conditions showed a steady increase in risk (respective odds ratios were 1.12, 1.42 and 1.62; P trend = 0.001) with adjustment for covariates including body mass index. Similar significant trends were observed in Filipina Americans (P trend = 0.021), postmenopausal women (P trend =0.001), Asian women who were born in the United States (US) (P trend = 0.052) and migrants who have lived in the US for at least 20 years (P trend = 0.004), but not migrants who lived in the US for <20 years (P trend = 0.64). These results suggest that westernization in lifestyle (diet and physical inactivity) and corresponding increase in adiposity have contributed to the rising prevalence of these metabolic conditions, which in turn, are associated with an increase in breast cancer. Abstract : What's new? Breast cancer incidence in Asian Americans is rising, for reasons that remain unclear. Possible factors involved include metabolic conditions such as high blood pressure, diabetes and dyslipidemia. In this case–control study of Asian–American women, history of metabolic conditions was associated with a significant trend in increasing breast cancer risk. Subgroup analyses revealed significant associations among Filipina Americans, postmenopausal women and Asian women who were born in the United States or who were long‐term US residents. The findings suggest that increase in metabolic disorders and breast cancer in these populations is linked to the adoption of a Western lifestyle.